Respuestas
Respuesta dada por:
1
Respuesta:
x1= 2
x2= 0.33
Explicación paso a paso:
3x² - 5x - 2 = 0
a=3
b= -5
c= -2
x= -b+-√ b²-4ac
2a
sustituyendo
x= -(-5)+-√ -5²-4(3)(-2)
2(3)
x= 5+-√ 25+24
6
x= 5+-√49
6
Soluciones
x1= 5+7 = 2
6
x2= 5-7. = -0.33
6
germanya200667:
muchas gracias
Respuesta dada por:
1
Respuesta:
ahí está el procedimiento....
Adjuntos:
![](https://es-static.z-dn.net/files/d96/62c9758173d43643cff615070ddbb6cf.jpg)
Preguntas similares
hace 3 años
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años